Theory of accounts : volume 2 - Valix, Conrado T.; Valix, Christian Aris M. (Manila, Philippines : GIC Enterprises & Co. Inc., 2015)
This book serve as a reviewer in Theory of Accounts in the Philippine CPA Licensure Examinations. It is prepared in accordance with the syllabus for Theory of Accounts issued and approved by the board of Accountancy.
PHILPCPA: Philippine CPA Licensure Examinations given by the board of accountancy -- AICPA: Uniform CPA Examinations given by the American Institute of Certified Public Accountants -- IAA: Adapted questions from various intermediate accounting textbooks -- ACP: Author constructed questions to exemplify Philippine standards not fully covered in CPA examinations -- PAS: Questions based on provisions of Philippine Accounting Standards.
Keywords: ACCOUNTING -- EXAMINATIONS, QUESTIONS ETC